Teaching with Technology: Unraveling Emerging AI Practices in the Classroom. Shortlisted for BEST PDW 2024 for MED at the Academy of Management, American. - Brady, Mairead; Fellenz, Martin (My University, 2024)
In line with the conference theme of "Innovating for the Future," our workshop offers a hands-on exploration of the dynamic AI landscape and its impact on management education. We aim to unlock fresh insights and evidence-based contributions that will shape a brighter future for both management educators and learners. As management educators, we stand at the forefront of this transformative AI wave, facing the challenge of aligning our pedagogical approaches with rapidly evolving technology. To address this challenge, our PDW provides practical insights and a comprehensive AI toolkit that participants can seamlessly integrate into their educational practices. Throughout this workshop, we will delve into the practical applications of AI in the classroom, offering valuable opportunities to explore and adopt best practices. Our goal is to equip MED members with the knowledge and tools needed to enhance student engagement, encourage innovative teaching methods, and navigate the AI-driven educational landscape effectively. This immersive experience will empower delegates to embrace AI's potential in education providing them with a ready-to-use toolkit of AI applications to enrich their teaching and enhance their students' learning journey. In an era of AI-enabled learning, we guide educators on how to consider and integrate AI into management education processes, delivering value to students and creating engaging learning experiences.
PRESENTED
Chicago, Illinois.
Keywords: Artificial Intelligence, Management Education, AI challenges in the classroom; Digital Engagement; Digital Humanities; ARTIFICIAL INTELLIGENCE; Artificial Intelligence and Higher Education; Artificial Intelligence in Teaching and Learning; Future of Management Education